Multi-component bi-super hamiltonian KdV systems - Yazici, D; Oguz, O; Oguz, Ö (IOP Publishing Ltd, 2001)
It is shown that a new class of classical multi-component super KdV equations is bi-super Hamiltonian by extending the method for the verification of graded Jacobi identity. The multi-component extension of super mKdV equations is obtained by using the super Miura transformation.
Keywords: Physics